Public libraries are also for adults: results of a survey of professional librarians in Spanish - García Gómez, Fco. Javier (Revista General de Información y Documentación, 2015)
The group of seniors is one of the sectors of the population whose presence in the Spanish society will increase in the coming years. Public libraries, as a center of services and resources of interest to the community, should consider this group as a preferred destination for the planning, design and deliver their service offerings. We present the results of a survey of Spanish public libraries to find out what services and resources of interest to the group of elderly service, the most common uses, and trends that can be expected in the short and medium term
Keywords: Library Resources; Library Services; Older People; Public Libraries; Spain.